2011
DOI: 10.1111/j.1365-3156.2011.02816.x
|View full text |Cite
|
Sign up to set email alerts
|

Endemic and opportunistic infections in Brazilian solid organ transplant recipients

Abstract: Opportunistic Infections in transplant patients have a wide spectrum and may vary from asymptomatic to severe infections with high mortality. A better understanding of the epidemiology of endemic pathogens and clinical manifestations can contribute to the establishment of an early diagnosis as well as correct treatment aimed at decreasing morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 37 publications
3
64
0
8
Order By: Relevance
“…We believe that this locally endemic diseases and socioeconomic aspects, as suggested in a national retrospective study of renal and hepatic transplant recipients at four transplant centers, demonstrated that a significant proportion of the patients (4.7%) had an opportunistic disease, mainly tuberculosis. 13 Another aspect that may be discussed is that the history of prophylaxis for opportunistic agents has not been evaluated, and may have an impact on the causes of ARF. In our study, for instance, pneumocystis was frequent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that this locally endemic diseases and socioeconomic aspects, as suggested in a national retrospective study of renal and hepatic transplant recipients at four transplant centers, demonstrated that a significant proportion of the patients (4.7%) had an opportunistic disease, mainly tuberculosis. 13 Another aspect that may be discussed is that the history of prophylaxis for opportunistic agents has not been evaluated, and may have an impact on the causes of ARF. In our study, for instance, pneumocystis was frequent.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Endemic diseases, mainly infectious, are relevant for solid organ transplants. 13 However, contemporary data from emerging countries regarding this complication in renal transplant patients are scarce. Thus, this study carried out in Brazil aimed to identify the main causes of ARF that led to the need for intensive care and the factors associated with hospital mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Batista et al (11) , in a retrospective analysis of 1,754 transplants, found only two cases of dengue, including one with hemorrhagic features. More recently, Nasim et al (6) studied 258 renal transplant patients with positive serology for dengue, wherein only 4% presented with severe disease.…”
Section: Casementioning
confidence: 97%
“…In a recent review of 1,754 renal and liver transplants from Brazil, only five cases of the visceral form were reported. 5 We report a case of NWL reactivation in the mucosal and cutaneous forms concomitantly in a kidney transplanted patient.…”
Section: Introductionmentioning
confidence: 94%